Si Mama sebagai Media Pembelajaran Interaktif Orientasi Mobilitas Sosial Komunikasi (OMSK) untuk Meningkatkan Kemandirian Peserta Didik Tunanetra - Nickita Kiki Praditya (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This best practice aims to describe the use of Si Mama as an interactive learning media for Communication Social Mobility Orientation (OMSK) which has an impact on increasing the independence of students with special needs. Si Mama is an acronym for Siap Mandiri Bersama. Si Mama is a medium created by the author himself to help blind students increase their independence. Si Mama is implemented in the OMSK class IX at SLB Negeri 1 Bantul. The method for writing best practices uses a qualitative descriptive approach. The stages in this best practice activity consist of the preparation stage, implementation stage and evaluation stage. The author gave a questionnaire to students regarding the evaluation of the use of Si Mama which was then analyzed and used as a basis for determining conclusions. Based on the results of the questionnaire, it is known that there is an increase in the independence of blind students in learning OMSK using the interactive learning media Si Mama. Previous students had less independence and less interactive learning. The needs and abilities for independence in one class. Students who had independence before using Si Mama media were only 48 to 75, using five indicators for very poor, less, sufficient, good and very good (independent). Based on these indicators, it is known that students independence using Si Mama can increase. Thus, it can be concluded that Si Mama is an interactive learning media that can increase the independence of students with special needs.